THE EFFECT OF LEADERSHIP AND WORK ENVIRONMENT ON WORK PRODUCTIVITY: STUDY OF BANK BUKOPIN KCU LAMPUNG EMPLOYEES - Elba, Riskina Agustin; Efendi, Nur; Saptiani, Fenny (Jurnal Kompetitif Bisnis, 2023)
This study aimed to find out the effect of leadership on work productivity of Bank Bukopin KCU Lampung employees , to find out the effect of work environment on work productivity of Bank Bukopin KCU Lampung enployees, and also to know the effect of leadership and work environment on work productivity of Bank Bukopin KCU Lampung employees. Also, this study applied quantitative research. Furthermore, this study was conducted from January to April 2023. The population and sample of study are 47 Bank Bukopin KCU Lampung employees. Moreover, primary and secondary data were used in this study. The data were collected by distributing the questionnaire to the employees. Then, it was analyzed by using multiple linear regression analysis. Based on the result of research, it can be concluded that leadership and work environment have positive and significant impacts on employees’ work productivity by 54,0% and it was impacted by other factors not examined in this study such as motivation, discipline, competence, and others.